Case report: 18F-FDG PET/CT skeletal superscan-like in an adult patient with acute lymphoblastic leukemia - Hu, Yu; Dai, Wenli; Wang, Peng; Feng, Yawen; Feng, Hui; Li, Jun (Frontiers in Oncology, 2024)
We herein describe a rare case of adult acute lymphoblastic leukemia with an 18florine-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) skeletal superscan-like appearance. The degree of bone marrow uptake was so intense that it far exceeded the level of physiological cerebral uptake and radiourinary activity. The distribution was remarkably similar to a superscan seen on skeletal scintigraphy. Skeletal superscans of 18F-FDG PET/CT have been reported in hematological diseases, solid tumors with extensive bone metastasis, and metabolic diseases. Thus, we reviewed the PET/CT images of cases reported, indicating that more homogeneous distribution, without primary tumor and specific mandibular and skull activity, may be suggestive of hematological diseases.